2022
DOI: 10.1029/2022je007210
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Subsurface Stratigraphy Northwest of Ascraeus Mons, Mars, Using the SHARAD and MARSIS Radar Sounders

Abstract: The Tharsis Montes volcanoes on Mars are the source of laterally extensive lava flows and other volcanic deposits generating a complex stratigraphy throughout the Tharsis Volcanic Province. We use SHAllow RADar (SHARAD) and Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) observations in a region northwest of Ascraeus Mons to determine the composition, density, thickness, and spatial distribution of these emplaced volcanic materials. We identified subsurface reflectors along 43 SHARAD and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…The permittivity is consistent with permittivities found in dry, basaltic lava flows on Earth (Campbell & Ulrichs, 1969;F. Ulaby et al, 1990), as well as with orbital radar derived values for lava flows on Mars (Carter, Campbell, Holt, et al, 2009;Shoemaker et al, 2022;Simon et al, 2014). We infer that the scattering structures are likely comprised of sharp edges or cavities within lava flow regimes.…”
Section: Scattererssupporting
confidence: 86%
See 2 more Smart Citations
“…The permittivity is consistent with permittivities found in dry, basaltic lava flows on Earth (Campbell & Ulrichs, 1969;F. Ulaby et al, 1990), as well as with orbital radar derived values for lava flows on Mars (Carter, Campbell, Holt, et al, 2009;Shoemaker et al, 2022;Simon et al, 2014). We infer that the scattering structures are likely comprised of sharp edges or cavities within lava flow regimes.…”
Section: Scattererssupporting
confidence: 86%
“…From orbit, the permittivity can be determined in regions where an independent measurement of the thickness of a particular layer is available. SHARAD (20 MHz center frequency) and MARSIS (1.8, 3, 4, and 5 MHz sounding modes) have estimated the permittivity of layers within the polar ice caps, buried ice deposits across Mars, and that of dry rocky materials such as lava flows and pyroclastic deposits (e.g., Carter, Campbell, Holt, et al., 2009; Carter, Campbell, Watters, et al., 2009; Ganesh et al., 2020; Shoemaker et al., 2022; Simon et al., 2014; Watters et al., 2007). Given the suggested igneous surface material of Jezero, the orbital permittivity studies for lava flows on Mars are most relevant for comparison with RIMFAX findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values inferred in this study are on the lower to middle end of the permittivities found by Carter et al (2009) and Shoemaker et al (2022) who investigated the properties of the flows west and northwest of Ascraeus Mons. Carter et al (2009) found that the northern flow has permittivity values between 6.2 and 17.3, with an average of 12.2.…”
Section: Sharad Investigationmentioning
confidence: 59%
“…(2009) and Shoemaker et al. (2022) who investigated the properties of the flows west and northwest of Ascraeus Mons. Carter et al.…”
Section: Sharad Investigationmentioning
confidence: 99%